2022
DOI: 10.1021/acsami.2c13299
|View full text |Cite
|
Sign up to set email alerts
|

Alignment Control of Smectic Layer Structures in Liquid-Crystalline Polymers by Photopolymerization with Scanned Slit Light

Abstract: Photoalignment control of hierarchical structures is a key process to enhance the properties of optical and mechanical materials. We developed an in situ molecular alignment method, where photopolymerization with the scanned slit light causes molecular flow, leading to two-dimensional precise alignment of molecules over large areas; however, the alignment control has been explored only on a molecular scale. In this study, we demonstrate this photopolymerization-induced molecular flow, enabling mesoscopic align… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…The FTIR spectra were gathered from 500 to 4000 cm –1 with a resolution of 4 cm –1 . The polymerization conversion of the sample was calculated by the following equation. ( 1 A P : C C / A P : C N A M : C C / A M : C N ) × 100 where A x : y ( x = P for polymer and M for monomer; y = bond types) is the absorbance of the stretching vibrations of CC at 1619–1651 cm –1 and that of the stretching vibrations of CN at 2197–2234 cm –1 . , Figure S4 shows the conversion of the sample films as a function of the exposure dose (= [light intensity]·[irradiation time]). Then, POM observations of all sample cells were performed to determine their LC properties at a temperature of 100 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The FTIR spectra were gathered from 500 to 4000 cm –1 with a resolution of 4 cm –1 . The polymerization conversion of the sample was calculated by the following equation. ( 1 A P : C C / A P : C N A M : C C / A M : C N ) × 100 where A x : y ( x = P for polymer and M for monomer; y = bond types) is the absorbance of the stretching vibrations of CC at 1619–1651 cm –1 and that of the stretching vibrations of CN at 2197–2234 cm –1 . , Figure S4 shows the conversion of the sample films as a function of the exposure dose (= [light intensity]·[irradiation time]). Then, POM observations of all sample cells were performed to determine their LC properties at a temperature of 100 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we reported that photopolymerization-induced mass transport can produce surface structures of several hundred nanometers in depth. Furthermore, we found that photopolymerization with scanning slit light causes mutual molecular diffusion between polymers and monomers and that the diffusion is maintained in a steady state by the scanning light, leading to a continuous molecular flow. Of particular interest here is that the molecular flow enables the alignment of polymer main-chain and side-chain mesogens along the flow direction, and the resultant polymer film has a flat surface without any change of surface topographies. This interesting phenomenon of photopolymerization induced by molecular diffusion has the potential for creating novel surface topography; however, its detailed investigation remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, scanning-wave photoalignment has been demonstrated as a dye-free route to LC patterning, yet it requires a specialized setup for light-rastering. [29,30] In both surface-and polymer-mediated processes, photoalignment is often accomplished using LPL exposure of samples in the nematic mesophase (i.e., elevated temperatures), [31] where the presence of directional order, yet lack of positional order enables cooperative molecular reorientation. Additionally, photo-alignment and/or -polymerization are often (although not exclusively [32] ) accomplished using multistep high energy (UV) and/or intensity (≥100 mW cm −2 ) irradiation, [11,15] providing opportunities for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembly of liquid crystals has attracted considerable attention as an approach to the development of functional soft materials. A variety of dynamic and ordered liquid crystalline (LC) materials have been obtained based on their responsiveness to external stimuli such as heat, light, and electric fields. Interactions on solid surfaces have also been used to induce ordering transitions of the dynamic LC assemblies. Active LC thin films have been developed for on-demand patterning with precise molecular alignment. The combination of self-assembly of liquid crystals with molecular recognition at the interfaces allows preparation of LC systems that respond to target molecules. In particular, aqueous/LC interfaces have been studied as platforms to recognize biomolecules because they can amplify biomolecular interactions into macroscopic optical signals. The control of self-assembly of bioconjugated amphiphilic molecules at the aqueous/LC interfaces remains a challenge, although understanding of the behavior of LC assemblies is advancing in terms of molecular shape, intermolecular interactions, and nanosegregation. ,, Intensive studies have focused on molecular-level phenomena at liquid and solid interfaces to understand relationships between molecular design and dynamic interfacial behavior. ,, …”
Section: Introductionmentioning
confidence: 99%